(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
All the tragedies under study end with the death of the tragic hero, an element apparently common to most tragedies, not only to Shakespeare's. In Shakespearean tragedies the death of the tragic hero is not an isolated event because it brings with it the death of almost all the other characters.